Isolation and identification of P(3HB-co-4HB) producing bacteria from various locations in Kuala Terengganu - Chai, Jun Meng; Manogiri Sadasivam; Sevakumaran Vigneswari (Penerbit Universiti Kebangsaan Malaysia, 2019)
Polyhydroxyalkanoates (PHA) is a microbial bioplastic accumulated as a storage material under limited growth conditions in the presence of excess carbon sources. The ever increasing concern towards the depletion of petroleum resources and problems with utilization of a growing number of synthetic plastics, PHAs are being considered as a potential substitute for production of conventional non-degradable plastics. PHAs have been developed as biomaterials with unique properties for many years. Among all types of PHA, copolymer poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] is widely sought after for biomedical application due to the biocompatibility, non-cytotoxicity and non-genotoxicity. Therefore, the aim of this study is to isolate and identify P(3HB-co-4HB) producers from water and soil sources in Kuala Terengganu. Samples of lake and soil were collected during November 2017 and then screened for P(3HB-co-4HB) producer. A total of 18 isolates were obtained, however only 5 isolates were identified as potential PHA producer. Interestingly, 3 isolates were confirmed as copolymer P(3HB-co-4HB) producer through gas chromatography analysis. These 3 isolated identified bacterial strain were Cupriavidus sp. TMT 11 with the highest 4HB molar fraction of 14.1%. The other 2 isolates were Acinetobacter sp. KPD 13 and Cupriavidus sp. PD 16. The properties of the copolymer P(3HB-co-4HB) produced by wide variety of bacteria isolated can be tailored for various biomedical applications.